2021
DOI: 10.48550/arxiv.2102.05020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive Factors of Kinematics in Traumatic Brain Injury from Head Impacts Based on Statistical Interpretation

Abstract: Brain tissue deformation resulting from head impacts is primarily caused by rotation and can lead to traumatic brain injury. To quantify brain injury risk based on measurements of accelerational forces to the head, various brain injury criteria based on different factors of these kinematics have been developed. To better design brain injury criteria, the predictive power of rotational kinematics factors, which are different in 1) the derivative order, 2) the direction and 3) the power of the angular velocity, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Therefore, we applied PCA to simplify our previously developed DLHM [27] and showed that the simplified models can accurately predict the MPS, MPSR and MPS×MPSR. Because of different impact conditions (e.g., helmeted or unhelmeted, head to head or punch), the head kinematics and the relationship between head kinematics and brain deformation varies largely across different impact datasets [33], [42]. As a result, the brain regions that often experience severe deformation also vary among the types of impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we applied PCA to simplify our previously developed DLHM [27] and showed that the simplified models can accurately predict the MPS, MPSR and MPS×MPSR. Because of different impact conditions (e.g., helmeted or unhelmeted, head to head or punch), the head kinematics and the relationship between head kinematics and brain deformation varies largely across different impact datasets [33], [42]. As a result, the brain regions that often experience severe deformation also vary among the types of impacts.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, to cover a broader range of head impacts, we included 3,161 impact data from four different impact sources: 1) 2,130 football-like impacts simulated by a finite element model of a Hybrid III anthropomorphic test device headform (ATD) (labeled as HM for head model) [26], [27]; 2) 302 college football impacts measured by the Stanford Instrumented Mouthguard (labeled as CF) [28]- [30]; 3) 457 mixed martial arts impacts measured by the Stanford Instrumented Mouthguard (labeled as MMA) [7], [31]; 4) 272 reconstructed impacts from the National Association for Stock Car Auto Racing (labeled as NASCAR) [32], [33].…”
Section: A Datasets: Head Kinematics and Brain Finite Element Modelmentioning
confidence: 99%